Design of Website-Based E-Modules for Islamic Religious Education Courses in Public Universities - Nina Ikhwati Wahidah; Agus Komarudin; Iskandar Iskandar (Peneliti.net, 2022)
The purpose of this essay is to provide website-based e-modules for online learning resources for Islamic religious education courses at public universities. Many learning procedures are currently built online, especially for remote learning, in the digital era. As a result, technology-enhanced innovation in education is required. One of them is the incorporation of technological resources into educational content. in order to make instructional materials interactive and accessible from each student's home. Students may learn independently wherever they are and anytime they want by fusing educational resources with technology. We combined the Rowntree model, the Hannafin model, and the Dick and Cary model of adaption development research design in this work. The steps of needs analysis, design, product creation, and evaluation are also included in the research process. Experts in learning design, material/content expertise, and learning media expertise served as the study's subjects. 100 pupils altogether, including (4) linguists and (5) students from the science and technology faculty. The distribution of questionnaires to the research subjects is the method used to acquire the data for this study. Following that, descriptive statistics were used to examine the data collected by the checklist questionnaire. The findings of this study show that the built website-based e-module is practical and useful for usage in the learning process